THE INFLUENCE OF COATING MATERIAL DIFFERENCE AGAINST ENCAPSULATION EFFICIENCY OF RED GINGER OLEORESIN - Jayanudin Jayanudin; Rochmadi Rochmadi; M. Kemal Renaldi; Pangihutan Pangihutan (ALCHEMY Jurnal Penelitian Kimia, 2017)
The purpose of this study was to determine the effect of different coating materials on the efficiency of red ginger oleoresin encapsulation and characterization of microcapsule surface. The encapsulation process begins by dissolving chitosan with 1 % (v/v) acetic acid and dissolving sodium alginate using aquadest to be used as a coating material. Red ginger oleoresin alginate included in the solution was stirred. The mixture entered into the chitosan solution and added tween 80 was stirred using a homogenizer to emulsify. The emulsion that forms included in the spray dryer to be converted into a powder of microcapsules, and then analyzes the encapsulation efficiency and surface morphology of microcapsules using scanning electron microscopy (SEM). Differences in the coating material used were chitosan, mixture of chitosan-alginate and mixture of chitosan-alginate-sodium tripolyphosphate (STPP). Weight ratio of red ginger oleoresin and the coating material were 1: 1, 1: 2 and 1: 3. The research results obtained were the highest encapsulation efficiency obtained from the coating material of the chitosan-alginate-sodium tripolyphosphate (STPP) at a ratio of 1: 3, namely by 85 %.